Facilitators, barriers and expectations in the self-management of type 2 diabetes—a qualitative study from Portugal. (June 2015) - Laranjo, Liliana; Neves, Ana L; Costa, Alexandra; Ribeiro, Rogério T; Couto, Luciana; Sá, Armando B
Abstract: Background: Patients with type 2 diabetes mellitus (DM) have a central role in managing their disease, but the effective adoption of self-management behaviours is often challenging. Objectives: The main objective of this study was to assess the facilitators, barriers and expectations in the self-management of type 2 DM, as perceived by patients. Methods: Patients with type 2 DM were recruited at the Portuguese Diabetes Association outpatient clinic, using a convenient sampling technique. Qualitative data was obtained using video-recorded focus groups. Each session had a moderator and an observer, and followed a pre-tested questioning route. Two independent researchers transcribed and analysed the focus groups. Results: Three major themes were identified: diet, physical exercise, and glycaemic control. Difficulties in changing dietary habits were grouped in four main categories: decisional, food quality, food quantity, and dietary schedule. Barriers related to physical exercise also included decisional aspects, as well as fatigue, muscle and joint pain, and other co-morbidities. Information and knowledge translation, as well as family and social ties, were commonly explored aspects across the three themes and were regarded as facilitators in some situations and as barriers in others. Conclusion : This study provided new insight on the barriers, facilitators and expectations in type 2 DM self-management, pointing out the importance of tailored guidance. Future research should explore interventions designed to promote and facilitate behaviour change in this population.